Radiological assessment of the PRF/BMSC efficacy in the treatment of aseptic nonunions: A retrospective study on 90 subjects. Issue 11 (November 2016) - Dallari, D.; Rani, N.; Sabbioni, G.; Mazzotta, A.; Cenacchi, A.; Savarino, L.
Abstract: Background: Nonunion is a major orthopaedic concern because of treatment difficulty, high costs and devastating effects on the patients' life quality. Therefore, there is interest in the use of bone substitutes and cell-based strategies to augment fracture repair. We aimed to verify if Platelet Rich Fibrin (PRF) added with bone marrow stromal cells (BMSC) was able to improve the reparative process in the aseptic nonunion, and to establish whether it was worthwhile with atrophic nonunion. The primary outcome was radiological union. As secondary endpoint, the healing time was assessed, and the radiological consolidation grade at each follow-up. Methods: We identified 113 subjects with tibia or femur nonunion and retrospectively created two groups. Group A was constituted by 56 subjects who underwent the standard procedure, i.e. Judet decortication with/out internal fixation devices, and opposite cortical homoplastic stick. In 57 patients, the standard procedure was modified by adding PRF and BMSC carried by homologous lyophilised bone chips (group B). The same surgeon performed all the operations. To our knowledge, no data are reported in the literature about such application. Since a "gold standard" for healing quantification does not exist, a new scoring radiological system was applied, at 1.5, 3, 6, 12 and 24 months after treatment. Results: At the final 24-month follow-up, the radiological union percentage was 94, 12 in group B and 95, 12% in group A. A decreased healing time was demonstrated in the presence of PRF/BMSC in comparison with the standard procedure. When we compared the radiological scores at each follow-up, we found that the PRF/BMSC combination significantly improved the consolidation grade at 1.5-, 3- and 6-month follow-up in femurs and at 1.5-month follow-up in tibiae. Furthermore, an improved consolidation grade was demonstrated in the atrophic subjects treated with adjuvants compared to atrophic patients treated with the standard procedure at 1.5-month follow-up. Conclusions: This study supports the concept that the use of PRF/BMSC, during the standard procedure, is effective in shortening nonunion healing time. It could allow an early mobilization of patients, minimizing suffering, and could be an effective tool to reduce the health-care costs resulting from this issue. Level of evidence: Therapeutic level III.